2013
DOI: 10.5194/tc-7-1017-2013
|View full text |Cite
|
Sign up to set email alerts
|

A regional climate model hindcast for Siberia: analysis of snow water equivalent

Abstract: Abstract. This study analyzes the added value of a regional climate model hindcast with respect to snow water equivalent (SWE) for Siberia when compared to SWE estimates from forcing NCEP-R1. In addition, we examine the discrepancies of simulated SWE to several recent reanalysis products (NCEP-R2, NCEP-CFSR, ERA-Interim). We apply the regional climate model COSMO-CLM (CCLM) to a 50 km grid spacing using NCEP-R1 as driving force to obtain a 63 yr (1948 to 2010) gridded dataset of historical SWE. Simulated regio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 55 publications
2
30
1
Order By: Relevance
“…In an intercomparison of RCMs over North America, Salzmann and Mearns (2012) showed that RCMs are able to improve significantly the annual snow cycle compared to the unrealistic low values of snow water equivalent depicted by NCEP-NCAR reanalysis. Also, Klehmet et al (2013) revealed that a 50-km RCM can improve snow water equivalent estimations compared to the forcing NCEP reanalysis over Siberia.…”
Section: Introductionmentioning
confidence: 98%
“…In an intercomparison of RCMs over North America, Salzmann and Mearns (2012) showed that RCMs are able to improve significantly the annual snow cycle compared to the unrealistic low values of snow water equivalent depicted by NCEP-NCAR reanalysis. Also, Klehmet et al (2013) revealed that a 50-km RCM can improve snow water equivalent estimations compared to the forcing NCEP reanalysis over Siberia.…”
Section: Introductionmentioning
confidence: 98%
“…Rockel and Geyer (2008) likewise emphasise the importance of the convection scheme when considering model setup modifications. Furthermore, Klehmet et al (2013) chose to reduce the minimal heat diffusion coefficient in their CCLM simulation over Siberia to reduce atmospheric mixing and obtain more realistic winter temperatures. Hence, a sensitivity study on the CCLM convection scheme and its tuning parameters should be performed for the study region.…”
Section: Discussionmentioning
confidence: 99%
“…Several downscaling studies for Central Asia do exist with horizontal grid spacing down to 20-30 km using different models (Gao et al 2011;Kim et al 2008;Klehmet et al 2013;Liu et al 2013;Mannig et al 2013;Maussion et al 2014;Sato et al 2007). These studies focus on future projections and/or the better representation of Asian monsoon dynamics in the RCM simulations.…”
Section: And Clemens Simmermentioning
confidence: 99%
See 1 more Smart Citation
“…Because the main glacier ablation period is in summer, the increase of the summer temperature causes an increase in the liquid precipitation but not in the solid precipitation, thus causing the glacier mass income to decrease and the glacier retreat to excelerate. 37 Mountain glaciers can modulate the river runoff and maintain a balance of the hydrological cycle. Glaciers are directly able to delay the runoff by preventing precipitation from running off.…”
Section: Discussionmentioning
confidence: 99%